Back Pain among Farmers in A Northern Area of China - Liu, Xiaotong (2012)
STUDY DESIGN: This was a population-based survey conducted in 2008 in a northern area of China. OBJECTIVE: To investigate back pain prevalence and to examine the associations between potential risk factors and back pain among Chinese farmers. SUMMARY OF BACKGROUND DATA: Few studies have investigated back pain and its associated risk factors among farmers in low-income and developing nations. METHODS: Farmers ages 15 years and older were chosen from 800 families in Heilongjiang Province of People’s Republic of China using cluster sampling methods. Complete survey data were obtained from 2045 farmers. The prevalence of self-reported back pain during the previous three-months was reported. Associations between back pain and potential risk factors were examined in logistic regression models which included age, gender, education levels, perceived stress, main farm activities, smoking, and drinking status. RESULTS: A total of 786 (38.4%) farmers reported back pain. Two-thirds of those with back pain (66.0%) reported that back pain affected work quantity and quality. The adjusted odds ratios of reporting back pain increased with advancing age. Females and farmers who experienced stress regularly were also more likely to report back pain. CONCLUSION: Back pain is a common problem among Chinese farmers and is reported more frequently by females. Significant positive associations of gender, age, and perceived stress with back pain warrant additional study.